DEFINSI AKUNTANSI DALAM BINGKAI MAQOSHID SYARIAH - Yopi Yudha Utama (Istithmar: Jurnal Studi Ekonomi Syariah, 2019)
The main concern of maqoshid shariah is to creating the benefit of the people or creating the benefit for all off the creatures . This concept is very appropriate in the world of accounting, because modern accounting is full of materialistic matters, which will create capitalistic life. capitalism causes the stronger party to get stronger, and the smaller parties suffer even more. Capitalistm is inhuman, because it can lead to exploitation either from human to other human beings, or the state to other countries. So, modern accounting must be changed, starting from the definition. Definition is an important thing, because of this definition will form the mindset to the practice. The writer uses qualitative research and uses a postmodern paradigm approach in the point of view of maqoshid shariah. Maqoshid syariah consists of three categories among them are like dharuriyyat, hajiyyat, and tahsiniyyat. The purpose of this research is to make a new definition of accounting based on maqoshid shariah. The results of this research is new accounting definition based on maqoshid syariah. The definition off accounting based on maqoshid syariah is a science that have to provide information to stakeholders and shareholders about the operational and the condition of the company both quantitatively and qualitatively without any engineering conditions in order to help create a harmonious life in all lining.